Optimisation on the Hybridisation Ratio of Pulverised Fuel Ash and Ground Granulated Blast Furnace Slag (PFA - GGBS) for the Fabrication of Geopolymer Mortar - Muhammad Hasnolhadi Samsudin; Wai Hoe Kwan; Putri Anis Syahira Mohamad Jamil; Nurhanim Abdul Aziz (Journal of Engineering Technology and Applied Physics, 2023)
The current cement industry has several environmental and social problems, including high greenhouse gas emissions, air pollution, water consumption, and the generation of large quantities of waste. This matter has grown into a significant concern, and there is now a pressing requirement to substitute the conventional binding material in concrete, namely Ordinary Portland Cement (OPC). This paper presents the report on the hybridisation of two industrial by-products, namely pulverised fuel ash (PFA) and ground granulated blast furnace slag (GGBS), to produce an alternative binder known as geopolymer. A set of 11 hybrid PFA-GGBS geopolymeric mortar mixes was created using the complete range of hybridisation ratios, along with different water-to-binder ratios. The freshly mixed hybrid PFA-GGBS geopolymeric mortar was put through a flow table test to examine the required water-to-binder ratio to achieve the targeted level of workability. Afterward, all the samples were allowed to cure at room temperature before undergoing a destructive test to measure their compressive strength. According to the study's findings, the highest compressive strength of 4.6 MPa was achieved with a PFA-GGBS hybridisation ratio of 60-40 in the geopolymeric mortar. However, when the content of GGBS exceeded 40 %, the compressive strength of the hybrid PFA-GGBS geopolymeric mortar produced tended to decrease. Additionally, as the replacement level of GGBS increased, the required water-to-binder ratio also increased to maintain the targeted level of workability, ranging between 0.31-0.41. The PFA-GGBS hybridisation ratios of 60/40, 50/50, 40/60, and 30/70 have shown promising properties to be further refined regarding their application in cementless concrete. Moreover, the study conducted to replace cement as a binder in concrete has the potential to make the construction industry more sustainable and reduce carbon emissions by utilising industrial waste ash that would need to be affordable, strong, durable, and widely available in order to be practical.